Complete Sequence, Analysis and Organization of the Orgyia leucostigma Nucleopolyhedrovirus Genome - Hilary A. M. Lauzon; Basil M. Arif; Lillian Pavlik; Robert I. Graham; Renée Lapointe; Christopher J. Lucarotti; David K. Thumbi; Robert J. M. Eveleigh (Viruses, 2011)
The complete genome of the Orgyia leucostigma nucleopolyhedrovirus (OrleNPV) isolated from the whitemarked tussock moth (Orgyia leucostigma, Lymantridae: Lepidoptera) was sequenced, analyzed, and compared to other baculovirus genomes. The size of the OrleNPV genome was 156,179 base pairs (bp) and had a G+C content of 39%. The genome encoded 135 putative open reading frames (ORFs), which occupied 79% of the entire genome sequence. Three inhibitor of apoptosis (ORFs 16, 43 and 63), and five baculovirus repeated ORFs (bro-a through bro-e) were interspersed in the OrleNPV genome. In addition to six direct repeat (drs), a common feature shared among most baculoviruses, OrleNPV genome contained three homologous regions (hrs) that are located in the latter half of the genome. The presence of an F-protein homologue and the results from phylogenetic analyses placed OrleNPV in the genus Alphabaculovirus, group II. Overall, OrleNPV appears to be most closely related to group II alphabaculoviruses Ectropis obliqua (EcobNPV), Apocheima cinerarium (ApciNPV), Euproctis pseudoconspersa (EupsNPV), and Clanis bilineata (ClbiNPV).